Oleander - Phua, Alvin Jun Ting (Nanyang Technological University, 2023)
Oleander is a 2D digitally hand-drawn animated short film depicting a tragedy caused by the act of infidelity and heavy alcoholism The objective of this film is to represent the distressing truth about abuse and ineffective ways of dealing with it. The storyline was created not only to shock the viewers but also to serve an underlying message on the severe consequences of recklessness. With the rising popularity of adult animations, I was very excited to utilize this opportunity to advocate for an adult animated short. Rather than approaching a stylized aesthetic, I wanted a slightly more realistic look to my characters. I felt that such a look could correspond with my target audience better. This Final Year Project (FYP) report documents the makings and process of this Oleander. From the core concept to the full production. It entails the many roles involved in production, covering the concept design, storyboards, character and background design to animating and compositing.